2021
DOI: 10.3390/ijms222111327
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines as Biomarkers in Systemic Lupus Erythematosus: Value for Diagnosis and Drug Therapy

Abstract: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease. The disease is characterized by activation and dysregulation of both the innate and the adaptive immune systems. The autoimmune response targets self-molecules including cell nuclei, double stranded DNA and other intra and extracellular structures. Multiple susceptibility genes within the immune system have been identified, as well as disturbances in different immune pathways. SLE may affect different organs and organ systems, and organ involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 86 publications
2
19
0
1
Order By: Relevance
“…Interferon- α has been a critical and the most studied cytokine in the pathogenesis of SLE ( 85 ). As is known about half of lupus patients have a predominant expression of interferon-induced genes in their peripheral blood mononuclear cells, which is an enhanced type I interferon gene signature ( 86 ). A cohort conducted at Karolinska observed that high IFN-α activity correlates positively with disease activity scores (SLEDAI and SLAM) and with the active involvement of specific organs: e.g., nephritis, arthritis, lymphadenopathy, fatigue, and weight loss.…”
Section: Molecular Mechanisms In Slementioning
confidence: 99%
“…Interferon- α has been a critical and the most studied cytokine in the pathogenesis of SLE ( 85 ). As is known about half of lupus patients have a predominant expression of interferon-induced genes in their peripheral blood mononuclear cells, which is an enhanced type I interferon gene signature ( 86 ). A cohort conducted at Karolinska observed that high IFN-α activity correlates positively with disease activity scores (SLEDAI and SLAM) and with the active involvement of specific organs: e.g., nephritis, arthritis, lymphadenopathy, fatigue, and weight loss.…”
Section: Molecular Mechanisms In Slementioning
confidence: 99%
“…This immune response provides the initial defense against invading pathogens [ 26 ]. The innate system involves skin, epithelial tissue linings, respiratory tract, and genitourinary tract, as well as the mucus layers that coat these tissues, and includes neutrophils, monocytes, macrophages, cytokines, and specific proteins [ 27 , 28 ]. Importantly, skin provides a solid and sturdy barrier for the internal milieu against environmental toxins, ultraviolet radiation, bacteria, and germs.…”
Section: Functional Importance Of the Immune System And Its Connectio...mentioning
confidence: 99%
“…Прогресс фундаментальных исследований, способствующих лучшему пониманию механизмов иммунопатологии СКВ, послужил теоретическим обоснованием для разработки новых подходов к фармакотерапии СКВ, в первую очередь генно-инженерных биологических препаратов (ГИБП) [44,[67][68][69][70][71][72][73], направленных на блокирование широкого спектра молекулярных и клеточных биологических «мишеней», участвующих в развитии воспаления и аутоиммунитета: цитокины и ИФН типа I, компоненты комплемента, внутриклеточные сигнальные пути и факторы транскрипции, модулирующие активность цитокинов и иммунометаболических процессов в клетках иммунной системы, патологическую активацию В-клеток и плазматических клеток (табл. 1).…”
Section: проблемы системной красной волчанки в XXI векеunclassified